2008
DOI: 10.1111/j.1945-5100.2008.tb00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Bulbous tracks arising from hypervelocity capture in aerogel

Abstract: Abstract-The capture of 81P/Wild 2 cometary particles in aerogel with a well-defined impact velocity (6.1 km s −1 ) has provided a wealth of data concerning the composition of Jupiter-family comets. To interpret this data we must understand the capture processes in the aerogel. A major category of tracks are those with bulbous cavities lined with particle fragments. We present a new model to account for the production of these "turnip"-shaped impact cavities. The model uses a thermodynamic approach in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 22 publications
5
79
0
Order By: Relevance
“…Projectile deceleration is accomplished through a complex combination of shock processes, a formidable problem in itself for highly porous media (e.g., Ahrens and Cole 1974), and viscous drag (Anderson and Ahrens 1994;Trucano and Grady 1995;Dominguez et al 2004;Trigo-Rodríguez et al 2008). Current modeling attempts are not possible without major assumptions regarding thermodynamic material constants at elevated pressures and other physical properties of aerogel, including its crushing strength under dynamic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Projectile deceleration is accomplished through a complex combination of shock processes, a formidable problem in itself for highly porous media (e.g., Ahrens and Cole 1974), and viscous drag (Anderson and Ahrens 1994;Trucano and Grady 1995;Dominguez et al 2004;Trigo-Rodríguez et al 2008). Current modeling attempts are not possible without major assumptions regarding thermodynamic material constants at elevated pressures and other physical properties of aerogel, including its crushing strength under dynamic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The success of mineral interpretation for terminal particles extracted from aerogel (e.g., Zolensky et al 2006), shows that larger grains pose no great problems. However, the admixture of aerogel and remnants of finer particles along aerogel tracks (Zolensky et al 2006;Trigo-Rodríguez et al 2008) suggests that it may be useful to determine the composition of smaller grains within the aluminium foil craters where the impactor material may be retained in a limited area, and not dispersed over a large volume as is the case in some Stardust aerogel tracks where the impactor has broken up during capture. In addition, particles collected by aerogel cannot be readily analyzed in situ, generally requiring extraction and preparation for examination.…”
Section: Introductionmentioning
confidence: 99%
“…Burchell et al (2009) have suggested an analysis of the tracks in the Stardust aerogel implies the aerogel on average behaved as if it had a mean density of just under 20 kg m −3 . Trigo-Rodríguez et al (2008) estimate peak shock pressures during capture in aerogel of 20 kg m −3 of just under 1 GPa. In its rapidity and thermal effects, aerogel capture amounts to shock processing and may have the dual effects of affecting both structure (via amorphization) and composition (via devolatilization) of cometary carbonaceous materials.…”
Section: Stardust Aerogelmentioning
confidence: 99%